2007
DOI: 10.1007/s00464-007-9307-8
|View full text |Cite
|
Sign up to set email alerts
|

Midterm outcome of radiofrequency thermal ablation for symptomatic uterine myomas

Abstract: RFA of symptomatic fibroids seems a valuable alternative to major surgery, with durable symptom relief for most patients and a low chance of recurrence at midterm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
2
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 26 publications
2
42
2
5
Order By: Relevance
“…Ghezzi and colleagues performed percutaneous RFA on up to three fibroids per patient in 25 women and followed them for 12 to 36 months. These patients all demonstrated symptomatic improvement and showed a mean 59% improvement in their quality of life with a 4% (1/25) reintervention rate at 1 year and as much as an 84% reduction in mean fibroid volumes at 36 months [9].…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Ghezzi and colleagues performed percutaneous RFA on up to three fibroids per patient in 25 women and followed them for 12 to 36 months. These patients all demonstrated symptomatic improvement and showed a mean 59% improvement in their quality of life with a 4% (1/25) reintervention rate at 1 year and as much as an 84% reduction in mean fibroid volumes at 36 months [9].…”
Section: Introductionmentioning
confidence: 93%
“…It has been shown that radiofrequency ablation results in heat/ thermal fixation and coagulative necrosis within the treated fibroids [9,10]. Recent studies have been performed using RFA in conjunction with simultaneous, real-time sonography to enable volumetric ablations that result in volume reduction and symptomatic relief [8,9,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Les symptômes et de la qualité de vie étaient significativement améliorés à partir de trois mois et pendant toute la durée de suivi : 10 mois. Ces femmes ont été revues au-delà d'un an avec des résultats inchangés, sauf une traitée par hystérectomie pour une récidive massive de myomes [17]. Elle associe cependant les risques de la coelioscopie à celui de la nécrose.…”
Section: L'embolisation Des Artères Utérinesunclassified
“…Medical therapy only an effect on the clinical symptoms based on long-term administration, and has adverse effects (6). A large variety of less invasive alternatives to hysterectomy have been developed, such as uterine artery embolization (UAE), high-intensity focused ultrasound (HIFU) and radiofrequency thermal ablation (7)(8)(9). Exposure to X-ray radiation is a persistent problem of UAE and may cause numerous complications (7).…”
Section: Introductionmentioning
confidence: 99%